(3eSGFd GdTjN GdWhSjs - (3GdWhSj, CHh LYaQ, eMeO Hf GdMSf Hf Ydj, J (B460(3g`s
(3ChdgG (B:s
(3ChdgG(B: (3eSCdI Yf bhd Gddg JYGdi(B: (3EfG YQVG GdCeGfI Ydi GdSehGJ hGdCQV hGdLHGd aGHjf Cf jMedfgG hCTabf efgGs
(3BNQgG (B:s
(3BNQgG(B: (3hfMf fbhd aj GdSbGW GdYbGH dCfgG gj GdMbjbI aj Pdc hgj eLGR aj RjGOI GdefGaY dbhd GdfHj(B: (3hYOOJ TaGYJj dCgd GdcHGFQ ef CeJjs
(3JHUQI GdYfhGf (B:s
(3PcQ aj GdPQjYI CcKQ ef YfhGf ddeSGFd, hdYd gPg GdQSGdI LRA ef EMOi GdYfGhjf GdePchQI aj GdPQjYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 84s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis